2010
DOI: 10.1037/a0018450
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel exploration of factors contributing to the overrepresentation of black students in office disciplinary referrals.

Abstract: Although there is increasing awareness of the overrepresentation of ethic minority students-particularly Black students-in disciplinary actions, the extant research has rarely empirically examined potential factors that may contribute to these disparities. The current study used a multilevel modeling approach to examine factors at the child (e.g., teacher-rated disruptive behavior problems) and classroom or teacher levels (e.g., teacher ethnicity, level of disruptive behavior in classroom) that may contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
204
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 280 publications
(217 citation statements)
references
References 61 publications
8
204
2
Order By: Relevance
“…Finally, in an ethnographic study of an urban school Morris (2005) found that administrators perceived Black girls to be unladylike and viewed Latino and Black boys as threatening; such biases contributed to higher dress code infractions among students of color. Unfortunately, these findings are supported by a growing body of evidence which suggests that racial disparities persist after accounting for student behavior and a range of confounding variables like poverty, disability, previous academic achievement, teacher-rated behavior, and school composition (Anyon et al, 2014;Bradshaw et al, 2010;Skiba, Michael, Nardo & Peterson, 2002;Skiba et al, 2014).…”
Section: Racial Disparities In Exclusionary School Discipline Practicesmentioning
confidence: 92%
See 2 more Smart Citations
“…Finally, in an ethnographic study of an urban school Morris (2005) found that administrators perceived Black girls to be unladylike and viewed Latino and Black boys as threatening; such biases contributed to higher dress code infractions among students of color. Unfortunately, these findings are supported by a growing body of evidence which suggests that racial disparities persist after accounting for student behavior and a range of confounding variables like poverty, disability, previous academic achievement, teacher-rated behavior, and school composition (Anyon et al, 2014;Bradshaw et al, 2010;Skiba, Michael, Nardo & Peterson, 2002;Skiba et al, 2014).…”
Section: Racial Disparities In Exclusionary School Discipline Practicesmentioning
confidence: 92%
“…The Relationship between Discipline Disparities and All Students' Connectedness Highly inequitable contexts, where racial discipline gaps are pronounced and visible to students, may contribute to lower connectedness to school adults among all students, not just youth of color or those who have been punished (Bradshaw et al, 2010;Gregory, Cornell & Fan, 2011;Morris, 2005;Vavrus & Cole, 2002). This hypothesis is supported by a small number of studies that have documented that students' perception of a hostile or unfair "racial climate" is associated with poorer outcomes for youth of all backgrounds (Bellmore et al, 2012;Debnam et al, 2013;Mattison & Aber, 2007).…”
Section: Racial Disparities In Students' Connectedness To School Adultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For students with challenging behaviors or those identified as E/BD there is a disproportionate representation of African American males across the United States and in Kentucky (USDOE, 2014;Wagner, Kutash, Duchnowski, Epstein, & Sumi, 2005). This data is in alignment with Kaufman et al (2001), who found that African American with students with E/BD had a greater number of office discipline referrals than any other student ethnicity group (Skiba, Chung, Trachok, Baker, Sheya, & Hughes, 2014;Bradshaw, Mitchell, O'Brennan, & Leaf, 2010). African American students were also found to have the highest percentage of suspensions, expulsions, and retentions compared to other ethnicity groups (Aud, Fox, et al, 2010).…”
Section: Students With Emotional and Behavioral Disorderssupporting
confidence: 64%
“…Although much of the literature on exclusionary discipline and disproportionality focuses on secondary-school settings (Bradshaw, Mitchell, O'Brennan, & Leaf, 2010), these phenomena have been observed at the elementary level as well. Shollenberger (2015) found that more Black boys were suspended prior to the fourth grade than any other demographic.…”
Section: Racial Discipline Disproportionalitymentioning
confidence: 99%